The effect of economic growth, inflation rate and interest rate on national savings in South Africa - Maja, Ramadimetja Boledi (My University, 2024)
Comprehending how macroeconomic variables affect national savings in South Africa is the primary aim of this study. The real rate of GDP growth, the rate of inflation, and the real interest rate are the macroeconomic variables employed in the study for the years 1980 through 2022. The variables taken into consideration in this study proved to be I(0) and I(1), according to the unit root test. To establish whether variables were cointegrated, the Autoregressive Distributed Lag (ARDL) bound test was used. Using the ARDL technique, the relationship between the long-term and short-term equilibrium was estimated. The standard Granger causality test was used to determine causality, and then the impulse response function (IRF) and variance decomposition were employed to forecast the macroeconomic variables. Cointegration test results demonstrated that the GDP growth rate, interest rate, inflation rate, and gross domestic savings had a stable long-term equilibrium relationship. The ARDL long-term results demonstrated that the gross domestic savings were significantly impacted negatively by the inflation. The real interest rate and GDP growth were not found to have a significant impact on gross domestic savings. In the short-term gross domestic savings were found to be significantly positively impacted by GDP growth, inflation rate, and the real interest rate. Further, the error correction term displayed that the model's speed of convergence to equilibrium was 21.19%. The diagnostic tests did not reject the null hypothesis and no causal relationship was found between gross domestic savings and explanatory variables. Lastly, the results from employing the impulse response function and variance decomposition to the variables showed that the inflation rate has the strongest influence on gross domestic savings over the long and short terms, followed by the real interest rate and GDP growth rate.
Thesis (M. Com. (Economics)) -- University of Limpopo, 2024
Keywords: Gross domestic savings; Real GDP growth rate; Inflation; Autoregressive Distributed Lag (ARDL); Impulse response; Interest rate; Casuality; Variance decomposition; Gross Domestic Product (GDP); Interest rates; Inflation (Finance) -- South Africa; Economic development -- South Africa